Results in the Latin America and Caribbean Region 2021, Volume 16 - World Bank (World Bank, Washington, DC, 2022)
This book showcases the many ways in which the World Bank is pushing the medium-term sustainable development agenda forward while dealing with the pressing health emergency response and the economic and human capital recovery challenges. Though hard and dramatic for millions of people across the region, the pandemic crisis now offers a unique opportunity to rethink the future of Latin America and the Caribbean.